Relationship between Diabetes and Cognitive Impairment by MMSE Scale - Thi Ngoc Bang, Tran; Doan Phuong, Nguyen; Quang Bay, Nguyen; Viet Hanh, Le; Thi Phuong Hai, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2, 2025)
Abstract : Diabetes has many complications in different organs, but complications related to cognitive impairment have received little attention and have been fully studied. The Mini-Mental State Examination (MMSE) is a useful, simple and effective tool widely used to screen for cognitive impairment. Objective : To describe the characteristics of type 2 diabetes patients at the Medical and Pharmaceutical University Hospital, University of Medicine and Pharmacy, Vietnam National University, Hanoi. To analyze some factors related to cognitive impairment through the MMSE score of the above study group. Subjects and methods : Cross-sectional study of 107 patients diagnosed with type 2 diabetes and meeting the inclusion and exclusion criteria for examination and treatment at the Medical and Pharmaceutical University Hospital from August 2024 to June 2025. Results : The average age of the study group was 69.74 ± 10.81. The majority had a high school education or higher, accounting for 65.4%. The proportion of subjects with depression was 16.8%, and sleep disorders were 76.6%. The average time of diabetes detection was 12.6 ± 7.6 years. The average value of fasting blood glucose was 7.89 ± 2.76 and HbA1c was 8.9 ± 1.97. The average score of the MMSE for the study subjects was 24.08 ± 3.65. 34.6% of the study subjects had cognitive disorders. Cognitive impairment was associated with age (age ≥ 70), education level, manual labor occupation, HbA1c ≥ 7.5, history of hypoglycemia or hypertension, and depression. The difference was statistically significant (p<0.05). There was no correlation between cognitive impairment and gender, blood glucose target, and time of diabetes detection (p>0.05). Conclusion : The majority of patients in the study were elderly, with average to high levels of education and occupation, reflecting the characteristics of the urban population. The rate of physical exercise was low, while the majority of patients had had diabetes for more than 5 years and had difficulty controlling blood glucose and HbA1c, with only about 14% reaching the HbA1c threshold < 7%. Hypertension and complications due to diabetes appeared at a high rate. In addition, mental health is also a prominent issue with significant rates of anxiety, depression and sleep disorders, contributing to reduced quality of life and affecting the effectiveness of disease control. The importance of regular screening and monitoring of cognitive function in patients with diabetes, especially in high-risk groups. Treatment strategies should not only focus on glycemic control but also need to comprehensively manage associated factors such as hypoglycemia, depression, hypertension and health education to improve quality of life and minimize the progression of cognitive impairment.